Being Tolerant in Diaspora: Indonesian Islamic Religiosity, Islamism, and Attitude Towards Other Groups Among Indonesian Community in Australia - Toyibah, Dzuriyatun; Hidayah, Nur; Ruswandi, Bambang; Mushoffa, Eva; Sajaroh, Wiwi Siti; Iqbal, Asep Muhamad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
This study analyzes how the Indonesian Muslim community in Australia coexists with non-Muslim communities and how their religiosity and the tendency of Islamism influence their interactions. An online survey was done to collect data by using a questionnaire involving 106 respondents, all members of religious study groups (pengajian) in Sydney. All items satisfy the criteria of validity with a correlation value greater than 0.3, and the construct is also reliable with α = 0.872, indicating good internal consistency. Analysis was done by means of Structural Equation Modelling (SEM) with R^2 =22.3%; the study shows that support for both religiosity and Islamism has a significant effect on attitudes toward other groups. Remarkably, Islamism is found to have a negative impact on positive attitudes towards non-Muslims (R1^2=19.15%), fortifying findings from similar research specifying that Islamists frequently oppose pluralism. In addition, the study suggests that performing obligatory rituals, such as Ramadan fasting and daily prayers, does not significantly affect positive attitudes towards non-Muslim groups (R1^2=0.052%). Nonetheless, distinct Islamic religious practices in Indonesia, e.g., yasinan, tahlilan, tasyakkuran, selametan, mawlid an-Nabi (celebrating the Prophet Muhammad’s birthday), and ziyarah, positively and significantly affect positive attitudes towards other communities in Australia (R1^2=3.055%). This reflects the nature of Indonesian Islamic religious practices that promote more tolerant and inclusive religiosity.